FAMADOGO OMO DANCE FOR US IN CEREMONY ENTERED A NEW HOME IN THE COMMUNITY NIAS - Sri Rahayu (Universitas Negeri Medan, 2015)
This study discusses forms of dance in the ceremony Omo Famadogo entering new homes in the community nias. The purpose of this study was to describe the form of dance ceremony Omo Famadogo entering new homes in Nias people. Theoretical foundation used in this research is the theory Sumandiyo Hadi and Suzan K. Langer with dance forms in complete unity. The population in this study is the dance Famadogo masyaraat Omo on Nias, artists, traditional leaders and dancers who know about dance Famadogo Omo, the sample in this study is the cultural figures and artists who know about art Famadogo Omo. Data collected by field work method that includes several steps, namely interviews, direct observation, documentation and literature study. The method used in this research is descriptive qualitative method. Based on the results of research conducted, that form of dance ceremony Omo Famadogo entering new houses on Nias community is a dance that test the strength and endurance on the building of new houses have been completed in the wake. This dance is a unified whole where this raw dance consists of nine varieties, which includes variation, repetition, movement, sequence, comparison, climax.